Comparison of Intravenous Indocyanine-Green and Inflation-Deflation Method in Lung Segmentectomy: A Meta-Analysis - Haidar Ali Robbani Al Asrory; Hana Imania (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Inflation-deflation technique had been a conventional method for delineating the intersegmental plane during lung segmentectomy. Over the last decade, the use of icg has shown a significant increase as an alternative method. According to the European Society of Thoracic Surgeons' (ESTS) newly released expert consensus recommendations, Systemic ICG is the preferred method for performing ISP delineation. Objective: This study aimed to determine the safety of intravenous ICG in lung segmentectomy compared to inflation-deflation method. Methods: PubMed, Science direct, and Scilit were systematically reviewed. Studies comparing ICG with inflation-deflation method in lung segmentectomy were included. The main outcome included operation time while blood loss, length of hospital stay, and air leakage event became secondary. Odd Ratio (OR) and Mean Difference (MD) with 95% of Confidence Interval (CI) were applied for dicotomous and continous variable, respectively. Heterogeneity was assessed using Cochrane Q and I statistics, as reviewers also manually tested for heterogeneity with sensitivity analysis. Results: Six studies with a total of 839 patients were retrieved. All of them were retrospective comparative studies, mainly with a diagnosis of pulmonary nodules. Most studies utilized peripheral vein injections of 2.5 mg/mL ICG solution, which had a dosage range of 3–10 mL. Intravenous ICG administration was associated with a noticable operation time [MD = -19.30, 95% CI -28.29 to -10.31, p < 0.00001], length of hospital stay [MD = -0.61; 95% CI -1.16 to -0.06, p = 0.03], as well as a significant OR observed in the number air leakage [OR = 0.39; 95% CI 0.20 to 0.75, p = 0.005]. Meanwhile, there was no significant difference in the amount of bleeding between the inflation-deflation group and the ICG group [MD = -5.18, 95% CI -12.08 to 1.72, p = 0.14]. Conclusion: This meta-analysis has demonstrated statistically that the duration of surgery, length of hospital stay, and the probability of postoperative air leak are significantly lower with the application of ICG in lung segmentectomy.